Ultrasound neuromodulation: a review of results, mechanisms and safety - Blackmore, J; Shrivastava, S; Sallet, J; Butler, C; Cleveland, R (Elsevier, 2019)
Ultrasonic neuromodulation is a rapidly growing field where low-intensity ultrasound (US) is delivered to nervous system tissue resulting in transient modulation of neural activity. This review summarises the fndings in the central and peripheral nervous systems from mechanistic studies in cell culture to cognitive behavioural studies in humans. The mechanisms by which US mechanically interacts with neurons and could affect firing are presented. An in-depth safety assessment of current studies shows that parameters for the human studies fall within the safety envelope for US imaging. Challenges associated with accurately targeting US and monitoring the response are described. In conclusion, the literature supports the use of US as a safe non-invasive brain stimulation modality with improved spatial localisation and depth targeting compared with alternative methods. US neurostimulation has the potential to be used both as a scientific instrument to investigate brain function and as a therapeutic modality to modulate brain activity.